University teachers’ attitudes towards English language curriculum of M.Ed. semester system - Paudel, Pitamber (Journal of NELTA, 2019)
A curriculum changes as per the concurrent philosophical and methodological changes of a country. This study investigates the Tribhuvan University (TU)teachers’ attitudes towards the current Masters level English language (semester system) curriculum. In order to achieve this goal, explanatory sequential mixed research design was employed. Forty-five English language teachers from both constituent and affiliated campuses of Tribhuvan University, Nepal, were purposively selected. The research shows that the university English teachers had positive attitude towards the current curriculum for its input and process. However, they did not like the context of its design and the implementation process. This implies that the policy maker and curriculum designers should make an analysis of the context in terms of situation and the needs of the stakeholders before selecting the courses and their contents so that the curriculum can be effectively implemented.